Tripterygium wilfordii Hook. F. and Its Extracts for Psoriasis: Efficacy and Mechanism - Wang Y; Tian Z; Huang S; Dang N (Dove Medical Press, 2023)
Yingchao Wang,1,2 Zhaochun Tian,3 Shuhong Huang,4 Ningning Dang1,2 1Department of Dermatology, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of China; 2Department of Dermatology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China; 3Science and Technology Innovation Center, Shandong First Medical University, Jinan, Shandong, People's Republic of China; 4School of Clinical and Basic Medical Sciences, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of ChinaCorrespondence: Ningning Dang, Department of Dermatology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, 324 Jingwuweiqi Road, Jinan, Shandong, 250021, People's Republic of China, Email dangningning@sdfmu.edu.cnAbstract: Psoriasis is an inflammatory autoimmune skin condition that is clinically marked by chronic erythema and scaling. The traditional Chinese herb Tripterygium wilfordii Hook. F. (TwHF) is commonly used in the treatment of immune-related skin illnesses, such as psoriasis. In clinical studies, PASI (Psoriasis Area and Severity Index) were dramatically decreased by TwHF and its extracts. Their benefits for psoriasis also include relief from psoriasis symptoms such as itching, dryness, overall lesion scores and quality of life. And the pathological mechanisms include anti-inflammation, immunomodulation and potentially signaling pathway modulations, which are achieved by modulating type-3 inflammatory cytokines including IL-22, IL-23, and IL-17 as well as immune cells like Th17 lymphocytes, γδT cells, and interfering with IFN-SOCS1, NF-κB and IL- 36α signaling pathways. TwHF and its extracts may cause various adverse drug reactions, such as gastrointestinal responses, aberrant hepatocytes, reproductive issues, and liver function impairment, but at adequate doses, they are regarded as an alternative therapy for the treatment of psoriasis. In this review, the effectiveness and mechanisms of TwHF and its extracts in psoriasis treatment are elucidated.Keywords: efficacy, mode of action, Tripterygium wilfordii Hook. F., psoriasis, type-3 inflammation